Fragment - Fahy, Warren (New York Delacorte Press, 2009)
Scientists have made a startling discovery: a fragment of a lost continent, an island with an ecosystem unlike any they've seen before... an ecosystem that could topple ours like a house of cards
Keywords: Biologists -- Fiction; Botanists -- Fiction; Evolution (Biology) -- Fiction; Island animals -- Fiction; Reality television programs -- Fiction; Adventure fiction; Suspense fiction